Efficacy of herbal mucoadhesive gel with extracts of Coriandrum sativum and curcumin as local drug delivery in the treatment of chronic periodontitis - A clinico-microbiological trial - Sachin G. Fulbel; Nikesh N. Moolya; Nilima S. Rajhans; Monali B. Pimple; Neha V. Kumthekar; Gaurav S. Lodha; Vivek R. Devani (Wolters Kluwer Medknow Publications, 2020)
Context: Herbal products are the recent advancement in the field of alternative medicines for the management of chronic periodontitis. They can be used as local drug delivery (LDD) agents over conventional antibiotics because of their extensive natural activity, advanced safety margin, and inferior costs. The present study evaluates the efficacy of one such indigenously prepared herbal gel containing extracts of Coriandrum sativum and curcumin in chronic periodontitis patients. Subjects and Methods: A total of 18 patients diagnosed with chronic periodontitis were included in this randomized clinical trial. The selected 72 pockets were equally divided into experimental and control groups. Full mouth scaling and root planing (SRP) was done. The experimental site received indigenously prepared herbal LDD gel containing combined extracts of C. sativum and curcumin, and the other side received a placebo gel. The periodontal parameters assessed were plaque index, papillary bleeding index, periodontal pocket depth (PPD), and clinical attachment level (CAL) at baseline, 1 month, and 3 months. Microbiological parameters for anaerobic analysis were assessed by colony-forming units at baseline and 3 months. Results: SPSS software analyzed all the data by repeated measure analysis of variance, paired t-test, and sample t-test with the difference of P < 0.05. Both clinical parameters and microbiological parameters showed a statistical reduction in the experimental group at 1 month and 3 months of evaluation. Significant better improvement was observed in the experimental group from 1 month to 3 months after the assessment in PPD and CAL. Conclusion: Locally delivered combined extracts of C. sativum and curcumin gel was more effective in reducing periodontal clinical parameter when used as an adjunct to SRP in the treatment of chronic periodontitis.